Arabic-Islamic views of the Latin West: tracing the emergence of medieval Europe - König, Daniel (Oxford University Press, 2015)
The author offers an insight into how the Arabic-Islamic world perceived medieval Western Europe, refuting previous claims that the Muslim world regarded Western Europe as a cultural backwater, instead arguing for the presence of cultural and information flows between the two very different societies